2000
DOI: 10.1038/sj.mp.4000650
|View full text |Cite
|
Sign up to set email alerts
|

Decreased in vitro production of interferon-gamma and interleukin-2 in whole blood of patients with schizophrenia during treatment

Abstract: A pattern of aberrations in the T-cell cytokine system that is typical for autoimmune disorders has also been reported in patients with schizophrenia, namely a decreased interleukin-2 (IL-2) production and increased levels of the soluble IL-2 receptor (sIL-2R). It has also been reported that the production of interferon-␥ (IFN-␥) may be lowered. In a longitudinal design, we studied the production of both IFN-␥ and IL-2 and their correlation in patients with schizophrenia during treatment and investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 78 publications
8
49
0
1
Order By: Relevance
“…Moreover, the copolymer glatiramer acetate (copolymer-1, Cop-1), a weak agonist of self-antigens, leads to the activation of T suppressor cells that can counteract the psychotomimetic effects of dizolcipine maleate (MK-801) and amphetamine (21). Overexpression of Egr2 and Egr3 has been shown to inhibit the transcription of IL-2 (20,22), and altered IL-2 regulation has been reported in schizophrenia (23,24). In addition to their downstream position in calcineurin signaling, EGR genes interact with a number of other factors implicated in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the copolymer glatiramer acetate (copolymer-1, Cop-1), a weak agonist of self-antigens, leads to the activation of T suppressor cells that can counteract the psychotomimetic effects of dizolcipine maleate (MK-801) and amphetamine (21). Overexpression of Egr2 and Egr3 has been shown to inhibit the transcription of IL-2 (20,22), and altered IL-2 regulation has been reported in schizophrenia (23,24). In addition to their downstream position in calcineurin signaling, EGR genes interact with a number of other factors implicated in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that the interface between these complex systems is impaired in schizophrenia (SCH, Altamura et al, 1999). Specially, SCH has been associated with several immunological abnormalities, including decreased mitogen-induced lymphocyte proliferation , altered numbers of total T and T-helper cells (Muller et al, 1993), the presence of antibrain antibodies in serum (Henneberg et al, 1994), and changes in cytokines and cytokine receptors in the blood and the cerebrospinal fluid (CSF) (Licinio et al, 1993;Rapaport et al, 1994Rapaport et al, , 1997Ganguli et al, 1994Ganguli et al, , 1995Maes et al, 1995Maes et al, , 1997Maes et al, , 2000Maes et al, , 2002Lin et al, 1998;Arolt et al, 2000;Zhang et al, 2002a, b). Together, these studies show that SCH is associated with significant immunological alterations, and activation of the inflammatory response system (IRS) is mediated, in part, by cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…6 The innate immune activation in schizophrenia has been based on the findings of increased monocyte numbers, increased activity of macrophage, increased proinflammatory cytokine levels such as IL-1, IL-6, IL-18 and tumor necrosis factor(TNF)-␣. [7][8][9][10][11] Schizophrenia is also characterized by a decrease in IL-2 production [12][13][14] and interferon(IFN)-␥, 7,15 traditionally classified as Th1 cytokines, and an increase in IL-4 16 and IL-10, 17,18 traditionally classified as Th2 cytokines. On the other hand, there have been reports of an increased Th1 system in schizophrenia, specifically an increased IL-2 level in plasma 19 and in cerebrospinal fluid 20,21 and increased production of IL-2 and IFN-␥.…”
Section: Introductionmentioning
confidence: 99%